NALISIS PROFITABILITAS PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015–2018 - Randy Alifianda; Nurjanti Takarini (IDEI: Jurnal Ekonomi & Bisnis, 2020)
The company was founded with the aim of getting maximum and sustainable profits. Profitability can be used to assess how well a company can survive in its business. So, the purpose of this research was to find out the effect of liquidity, leverage, and activities in increasing profitability. The sample selection technique used in this research was purposive sampling. Samples obtained were 17 food and beverage companies listed on the Indonesia Stock Exchange in the 2015–2018 period. The data used in this research were secondary data obtained from the Indonesia Stock Exchange. The data analysis technique used in this research was multiple linear regression analysis. Based on the results of research that had been investigated, it can be concluded that leverage calculated using Debt to Assets Ratio was not able to contribute to profitability. Liquidity calculated using Current Ratio and Activities calculated using Total Assets Turnover Ratio can contribute to profitability.